Institutionalized Ignorance: Corporate Unresponsiveness to Environmental Safety in Russia - Villo, Sofia (Journal of Economic Sociology, 2018)
Many companies demonstrate low corporate responsiveness to environmental safety. The existing literature indicates egoistic behavior of companies as the main cause of low corporate responsiveness. However, these conclusions are based on cases from developed countries. What determines the low corporate responsiveness to environmental safety in developing and transition economies, for which the very concept of environmental business responsibility is new? In order to answer this question, this article examines the experience of one of the largest Russian oil companies in ensuring environmental safety in the development of an oil field located on the territory of Russia. The information base of the research include documented sources of information, as well as in-depth interviews with managers of the Russian oil company, who make decisions about the environmental safety of the project as well as with external experts who cooperate with this company in the field of environmental safety. The results of the study showed that the low responsiveness to environmental safety of Russian companies is not due to their selfish behavior, as the existing literature suggests, but due to illiteracy of their top managers in environmental issues (lack of understanding of environmental safety issues). Via the approach of R. Whitley, the author of this research explains this illiteracy as the cognitive derivative of the national business system. The author shows that illiteracy of top managers in environmental issues is supported by the Russian culture, the Russian education system, and by financial and political systems. A theoretical explanation is offered of how environmental irresponsibility is formed within the context for which the very concept of environmental business responsibility is new. Speaking about the role of the political system in this process, governmental intervention in decision-making on environmental safety and the work of regulatory authorities are discussed.